2003
DOI: 10.1029/1999jc000288
|View full text |Cite
|
Sign up to set email alerts
|

Major nutrients and dissolved oxygen as indicators of the frontal zones in the Atlantic sector of the Southern Ocean

Abstract: [1] The chemical tracers of the main frontal zones of the Atlantic sector of the Southern Ocean are considered. Before the beginning of the spring bloom, frontal zones are distinguished by lateral gradients of dissolved oxygen, phosphate, nitrate, and silicate. During the spring bloom, the smoothing of nutrient concentrations on both sides of the fronts weakens lateral gradients of chemical properties. The position of surface gradients of nutrients within the Subtropical Frontal Zone (STFZ) does not coincide w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…The SAF in our study section was found near 46 • S (Fig.2). This location is consistent with previous studies (Hofmann, 1985;Belkin and Gordon, 1996;Dafner, 2003;Yuan et al, 2004;Aoki et al, 2007). The path of the SAF shows a general southward displacement in the Southern Indian Ocean (Orsi et al, 1995;Belkin and Gordon, 1996).…”
Section: Fronts In the Section I09s Along 115 • Esupporting
confidence: 90%
See 1 more Smart Citation
“…The SAF in our study section was found near 46 • S (Fig.2). This location is consistent with previous studies (Hofmann, 1985;Belkin and Gordon, 1996;Dafner, 2003;Yuan et al, 2004;Aoki et al, 2007). The path of the SAF shows a general southward displacement in the Southern Indian Ocean (Orsi et al, 1995;Belkin and Gordon, 1996).…”
Section: Fronts In the Section I09s Along 115 • Esupporting
confidence: 90%
“…Here we use the phenomenological criteria to identify oceanic fronts in the Southern Ocean, i.e., adopting the quasi-permanent nature of frontal properties (Dafner, 2003).…”
Section: Fronts In the Section I09s Along 115 • Ementioning
confidence: 99%
“…Holm‐Hansen et al ., ; Sokolov and Rintoul , ]. In open water, the timing and intensity of the spring bloom varies greatly, probably on account of water mass interactions [ Dafner et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The seasonal ice zone (SIZ) extends hundreds of kilometers from the Antarctic coast [ Sakshaug et al ., ] with sea ice typically being less than 1 m thick [ Pfaffling et al ., ] and growing from April and melting from October. The offshore water masses are characterized by latitudinal gradients in nutrients during the winter, which reflect the circumpolar frontal structure [ Dafner et al ., ]. The major fronts are found at 40°S (sub‐tropical front), 45°S (sub‐Antarctic front), 50°S (Antarctic polar front), and ca.…”
Section: Introductionmentioning
confidence: 99%
“…A primary difficulty when working with autonomous surface drifters is how to characterize their location with respect to hydrography. Multiple criteria have been defined to identify hydrological fronts, based either on vertical properties (Orsi et al 1995;Belkin and Gordon 1996) or on surface properties (Dafner et al 2003). In this paper, we test several methods for identifying the subantarctic front (SAF) from satellite data based either on sea surface temperature (SST) or on sea-level anomaly gradients.…”
mentioning
confidence: 99%